USP25 promotes endotoxin tolerance via suppressing K48-linked ubiquitination and degradation of TRAF3 in Kupffer cells. (February 2019) - Wen, Jian; Bai, He; Chen, Nan; Zhang, Wenfeng; Zhu, Xiwen; Li, Peizhi; Gong, Jianping
Highlights: USP25 has physical interactions with TRAF3. USP25 prevents ubiquitination and degradation of TRAF3 in Kuppfer cells. Stable expression of TRAF3 blunts inflammatory response. The USP25-TRAF3 pathway is critical for endotoxin tolerance. Abstract: The inhibition of tumor necrosis factor receptor-associated factor 3 (TRAF3) degradation induces endotoxin tolerance (ET) in macrophages. However, the mechanisms leading to TRAF3 inhibition by ET are largely unknown. Here, we found that ubiquitin-specific peptidase 25 (USP25), a deubiquitinating enzyme (DUB), interacted with TRAF3 and stabilized ET in Kupffer cells (KCs). Lentiviral knockdown of USP25 activated K48-linked ubiquitination of TRAF3 and the cytoplasmic translocation of the Myd88-associated multiprotein complex in tolerized KCs. This outcome led to a subsequent activation of Myd88-dependent c-Jun N-terminal kinase (JNK) and p38-mediated downregulation of inflammatory cytokines. The overexpression of TRAF3 attenuated the proinflammatory effects of USP25 knockdown in tolerized KCs. Thus, our findings reveal a novel mechanism of endotoxin-mediated TRAF3 degradation in KCs.